2010
DOI: 10.1080/02640414.2010.515238
|View full text |Cite
|
Sign up to set email alerts
|

The defence technique in Tai Chi Push Hands: A case study

Abstract: Developed from traditional Chinese martial arts, Tai Chi exercise includes different forms and interactive Push Hands but biomechanical analyses have focused on the former only. To analyse the techniques of Push Hands, an experienced master was asked to defend pushing by four opponents. Movements were videotaped and digitized using a motion analysis system. Surface electrodes were used to record the electromyographic activity of ten muscle groups. Two force plates were used to measure the ground reaction force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Tai Chi Master Xin Chen said that the elbow should be driven by hand, the shoulder by elbow, the lower knee by the feet, and the thigh by the knee [20]. From the sequence of the maximum angular velocity of the shoulder elbow joint angle in the master group, the angular velocity of the hand reached the maximum peak at about 41% of the time, the elbow joint followed by about 45%, and the shoulder joint reached the maximum peak of about 55%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tai Chi Master Xin Chen said that the elbow should be driven by hand, the shoulder by elbow, the lower knee by the feet, and the thigh by the knee [20]. From the sequence of the maximum angular velocity of the shoulder elbow joint angle in the master group, the angular velocity of the hand reached the maximum peak at about 41% of the time, the elbow joint followed by about 45%, and the shoulder joint reached the maximum peak of about 55%.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars think that the strength of Tai Chi is force with storage [21]. Strength storage is the prerequisite and necessary condition for strength, and strength is the ultimate goal and inevitable result of storing strength [20]. The boxing theory explains that strength storage is as opening a bow and forcing strength as an arrow.…”
Section: Discussionmentioning
confidence: 99%
“…The unique coordinated movements of tai chi are associated with significant effects on improving strength and endurance of the skeletal muscle and ameliorating proprioception and neuromuscular control function in older adults [2][3][4]. Previous studies have found that implementation of the push hands and wild horse's mane techniques of tai chi could be an optimal strategy to improve balance and prevent falls [5][6][7]. Compared with high pose, low-pose tai chi can elicit greater energy consumption and muscle activity [8,9], thus leading to better exercise efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Several biomechanical studies of TCC have been performed previously. Training in TCC includes the movement of qi , which requires “soft inside hard power and Jin inside soft power.” As the sequence of movements in the practice of TCC is very important, in order to provide students with a reference for the practice of TCC, Chen et al [ 23 ] used several techniques to study the movement of the center gravity during TCC instruction. They recorded images during the practice of TCC by an instructor and analyzed the movement.…”
Section: Introductionmentioning
confidence: 99%
“…They recorded images during the practice of TCC by an instructor and analyzed the movement. Using surface electrodes to record muscle contractions and force plates to measure biophysical parameters, their study observed the shift of body weight during TCC [ 23 ]. On the other hand, Wu and coworkers [ 24 ] focused on the muscle action patterns during TCC exercise, including the tibialis anterior, soleus, peronaeus longus, rectus femoris, semitendinosus, and tensor fasciae latae.…”
Section: Introductionmentioning
confidence: 99%